Variability During Training Sessions to Develop Coordination Skills in the Development of Tennis Players - Sanz, David; Fernandez, Jaime; Zierof, Pedro; Méndez, Alberto (ITF Coaching & Sport Science Review, 2012)
This article discusses a transversal methodology to develop the different coordination skills as applied to tennis. We consider this work to be relevant because of its cognitive implication for the performance of different coordination skills. The tennis player on-court, is constantly performing a series of technical activities that require different coordination skills, but he is also in a continuous process of decision making, which is constantly “contaminated” by uncertainty. It is an unquestionable reality that the specificity of the tasks involved in the training process is a key variable to its success. The specificity in the tasks is determined by the knowledge of the coach about fundamental learning and its timely sequence along the coaching process.